The Cinematic Poet on the Edge of the City: A Discussion on Jia Zhangke's Documentary Aesthetics - Liu, Kaiqi (Transactions on Economics, Business and Management Research, 2023)
Director Jia Zhangke's documentary visual aesthetics, while rooted in realism, emphasizes a subversion of tradition, navigating between realism and idealism. Among the sixth generation of directors, Jia Zhangke places a distinct emphasis on fragmented narrative characteristics. Without overly highlighting causal logic in the unfolding of stories, he intentionally slows down the narrative pace to reflect on reality. This paper, by examining his series of works, analyzes his enduring pursuit: exploring reality while maintaining the authenticity of life, achieving a documentary aesthetics that juxtaposes the unity of artistic truth and the truth of life.